Path way for Critical review on early prediction of bone density through various techniques - S, S Ashmad; G P Ramesh (Journal of Medical Biomedical and Applied Sciences, 2022)
Recent advancements in medical applications like detecting bone density in early stages is utmost necessary to save human lives. In this connection finding the amount of mineral or calcium content present in the bone or bone tissue plays a critical role, for that Bone Densitometer are utilizes to find exact values of Bone Mineral Density (BMD) or Bone Density which gives information about the structure of bone. Generally, Bone Densitometer gives two forms of results one is T-score and the other is Z-score. If the value of T-score or Z-score is less than the threshold value, then the density of bone is reduced and it will lead to chances of bone fracture. Frequently used bone densitometers are like Dual Energy X-ray Absorptiometry (DEXA) and Radiographic machines like CT and MRI. This review arcticle describes the volumetric and critical review on various techniques exists so far to determine the bone density from these it was observed that CT and MRI are most expensive and it generates more radiation which causes problems for human. Till now in literature the recorded accuracy with these methods are low. Finally the inference drawn from literature had given a thought that the usage of normal X-Ray machine when compared to existed methods may give better accuracy.